Africa: the Exhaustion of Electoral Democracy against the Resurgence of Presidential Third Termism and beyond? - Rupiya, Martin Revayi (Africana Studia, 2020)
In the post 1990s era of multiparty democracy in Africa, concerted attempts towards power retention by incumbents through ‘Third-termism’ has presented the most daunting challenge. Employing the development theory of testing case studies, this article examines progress made on the continent since the adoption of competitive multiparty democracy since the 1990s. Citing democratic stagnation in Togo, Gabon, Cameroon and other related states, the research reveals that sitting regimes have mastered the art of undertaking constitutional electoral processes without changing the outcome. This is a phenomenon that appears to have escaped the attention of researchers and analysts. The conclusion drawn is that, the quest for ‘Third-terms extending periods in power by long-serving incumbents and some surviving siblings has become the syndrome that reflects the embedded deep states which are immune to electoral challenge for the foreseeable future.